Behavior of two-way reinforced concrete voided slabs enhanced by steel fibers and GFRP sheets under repeated loading - Adel A. Al-Azzawi; Shahad H. Mtashar (Results in Engineering, 2023)
Moderately thick voided slab systems are used in the construction of long-span slab buildings to incorporate lower weight on foundations and enhance the thermal and sound insulation of the slab. In some cases, these slabs required an enhancement if there is an increase in the applied loads or a defect in their construction properties. This research is focused on giving better enhancement techniques for such cases with keeping the flexural ductile failure of the tested slabs. Eight slab specimens of (1000 × 1000 mm2) were cast and tested as two-way simply supported slabs. The tested specimens consist of one solid slab and seven voided slabs. The study variables comprised the nature of the slab (solid and voided), the thickness of the slab (100 and 125 mm), the presence of steel fibers (0% and 1%), and the number of GFRP layers. The voids in slabs were made using high-density polystyrene of dimensions (200 × 200 × 50 mm) with a central hole of dimensions (50 × 50 × 50 mm) to give the shape of donat. These voids are made at the ineffective concrete zones to give a reduction in weight by (34%–38%). The slabs were tested as simply supported slabs under partial uniform repeated loading. The results of tested specimens showed that the enhancement with a combination of steel fibers and GFRP sheets gave the least deflection (4.2 mm), higher ultimate loading capacity (150 kN), larger stiffness at cracking, and at ultimate load (52.5, and 35.7 kN/mm) respectively, more ductility index (1.35), and larger energy absorption (1098.7 kN mm)..At the same stage of loading, the effect of adding steel fibers by (1%) for voided slab leads to a decrease in the deflection by (30%) and increase the ultimate loads by (31%). Therefore the strengthening technique adopted in this research enhances the behavior of moderately thick voided slabs effectively and preserves a ductile flexural behavior.